MOTIVATIONAL FACTORS TO PROMOTE STUDENTS’ INTEREST AND INVOLVEMENT IN TEACHING-LEARNING ENGLISH - Win, Moe Moe (PEOPLE: International Journal of Social Sciences, 2018)
There are many problems in English language teaching as Second Language Learning. Among them, the most common problem found in students is lack of motivation and lack of student’s interest. To be effective teaching and learning, student’s emotion and tendency is necessary. As teacher understands how important the motivation and their interest are, various kinds of teaching methods and strategies have been applying in the foreign language educational field. Therefore, this paper suggests how to arouse the student’s interest through wholehearted support classroom environment and relevant activities. External motivational factors such as teacher’s teaching style, understanding of students’ level and their difficulties, relevant lesson plans, positive teacher-student relations are helpful for teacher to reduce students’ anxiety and negative attitude in learning. Similarly, activities such as Warm-up activities, creating Story with the students (for writing and speaking skills with role play), and activities in teaching learning English help them to activate. Improving motivation makes students and teachers good learning outcome.